2001
DOI: 10.1303/aez.2001.475
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of methyl anthranilate and its related compounds to the flower thrips, Thrips hawaiiensis (Morgan), T. coloratus Schmutz, T. flavus Schrank and Megalurothrips distalis (Karny) (Thysanoptera: Thripidae).

Abstract: Methyl anthranilate, a common flower volatile component, was found to be a potent attractant for four species of flower thrips, Thrips hawaiiensis, T. coloratus, T. flavus, and Megalurothrips distalis, irrespective of sex. Methyl anthranilate attracted significantly larger numbers of these four species than p-anisaldehyde, an already-known attractant for several species of flower thrips. The attractiveness of the related compounds varied between the species: Within 13 related compounds; two positional isomers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In the present study in sweet corn and broccoli, not only were beneficial Hymenoptera attracted to HIPV‐treated plants, but so were thrips, although these were only identified to order, comprising mainly herbivorous species. Several studies have demonstrated the attraction of several thrips species to Be (Teulon et al , 1993, 2007; Koschier et al , 2000), MeA (Imai et al , 2001) and MeSA (Teulon et al , 2007). By contrast, James (2005) did not find attraction to Be by Frankliniella occidentalis (Pergande) (Thysanoptera: Tripidae), which was abundant in that field study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study in sweet corn and broccoli, not only were beneficial Hymenoptera attracted to HIPV‐treated plants, but so were thrips, although these were only identified to order, comprising mainly herbivorous species. Several studies have demonstrated the attraction of several thrips species to Be (Teulon et al , 1993, 2007; Koschier et al , 2000), MeA (Imai et al , 2001) and MeSA (Teulon et al , 2007). By contrast, James (2005) did not find attraction to Be by Frankliniella occidentalis (Pergande) (Thysanoptera: Tripidae), which was abundant in that field study.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast to those studies, which identified attraction of natural enemies and increased parasitism, Orre et al (2010) found that not only the beneficial target species at the third trophic level was attracted to deployed MeSA in a turnip crop, but also Scaptomyza flava (Fallén) (Diptera: Drosophilidae) at the second trophic level and Anacharis zealandica (Ashmead) (Hymenoptera: Figitidae) at the fourth trophic level. Furthermore, herbivorous thrips have exhibited attraction to synthetic HIPV compounds (Teulon et al , 1993, 2007; Imai et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Blue and yellow sticky traps are used to monitor thrips population numbers and map their spread within a given area (Shipp 1995 ; Pearsall, 2002 ; Broughton & Harrison, 2012 ). The addition of certain chemical lures to these traps can significantly increase thrips catch, both in fields and glasshouses, sometimes by as much as 100 times (Kirk, 1985 ; Teulon et al ., 1993 ; Murai et al ., 2000 ; Imai et al ., 2001 ). Increases in trap attraction of F. occidentalis as a result of odour lures have been observed on a variety of crop types including but not limited to; pepper (Harbi et al ., 2013 ; Teulon et al ., 2014 ), bean (Niassy et al ., 2012 ; Muvea et al ., 2014 ), nectarine (Teulon et al ., 2014 ) and strawberry (Sampson and Kirk, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results clearly demonstrated a very high (even significant at 0.3 mg/kg) dose‐dependent analgesic activity for the anthranilates, and these at least partially justify the ethnopharmacological use of C. ternata (Radulović et al ., ). Methyl N ‐methylanthranilate ( M ), known for its high impact in the aroma of mandarins (Fanciullino et al ., ; Wilson and Shaw, ), has been attributed with the attractiveness to Mexican fruit flies (Massa et al ., ) and thrips (Imai et al ., ), as well as the repellency in bird species (Clark et al ., ; Schafer et al ., ), which suggests that M might have an influence on the CNS.…”
Section: Introductionmentioning
confidence: 99%